Effectiveness of Indigenous Bacteria of Salt-Washing Wastewater (Bittern) As Plastic Waste Degraders - Saputri, Wahyu Dwi; Ardani, Aliefia Miftakhul; Junaedi, Abdus Salam; Triajie, Haryo (Universitas Airlangga, 2025)
Plastic is a man-made synthetic polymer that has stable and durable characteristics The process of decomposing plastic takes a long time and the use of plastic which is increasing every year results in the accumulation of plastic waste in the environment, causing environmental pollution. Biodegradation is one solution to reduce the amount of plastic with the help of microorganisms or bacteria. This study has an objective to analyze the OD value; TPC; and the percentage value of plastic waste weight loss from each Indigenous bittern bacterial isolate in degrading plastic waste on YEB media + 1% glucose. The research procedure includes sterilization of tools and materials until data analysis. Data on TPC and OD values during the degradation process were analyzed descriptively and the percentage value of plastic dry weight after 7 days of incubation time was analyzed statistically. The highest OD value was 1,613 (BB1), the highest TPC value was 13,93 Log CFU/ml (BB4), and the highest plastic dry weight percentage value was 25%+0b (BB4). This research provides new insights into the potential of Indigenous bittern bacteria as plastic waste biodegradation agents and enriches knowledge in the field of environmental biotechnology. This research can be used as a basis for the waste management industry and government to design more sustainable policies in waste management to reduce dependence on conventional methods that are expensive and less effective